EFFICIENT MANAGEMENT PRACTICES FOR IMPROVING CARE & SANITATION FACILITIES OF PUBLIC HEALTHCARE DELIVERY SYSTEM: A CASE STUDY IN INDIA - Debnath, Reeti; Ray, Sumati (LIFE: International Journal of Health and Life-Sciences, 2018)
In spite of being one of the fastest growing economies of the world, and having taken steps to improve the country’s health status after independence, India still has a long way to go. The healthcare system is challenging in India, particularly because of huge population size, economic and social factors coupled with the rising burden of both communicable and non-communicable diseases. Capital and technology perhaps are the most necessary conditions for achieving health gains, but experience in many countries confirms that they are not sufficient. Organizations must combine financial, physical and human resources for better performance. Public hospitals are heavily utilized by lower income groups of the society, up to ninety percent in case of free patients. While this is a good indication of the level of access of people to public health facilities, this also casts an obligation on the Government to improve their infrastructure and systems. Reports of numerous patients dying due to lack of oxygen supply in wards or wrong sterilization procedures, patients delayed admission and treatment due to shortage of medical staff or unavailability of necessary drugs and equipments in the hospital is prevalent. The primary objective of this paper is to investigate the quality of sanitation and care of a tertiary level public healthcare facility in India. Data was collected from the inpatients and support staff of the hospital by using standard instruments. All ethical guidelines were fulfilled. Infrastructural scarcity and manpower allocation were a major issue. Staffs were significantly more negative in rating many aspects of hospital services. The researcher recommends accountability based work environment, periodic training modules for health workers, policy and infrastructural changes for improvement of the healthcare facilities.